Design strategies for urban and building adaptation in environmental multi-risk scenarios - Mario Losasso; Sara Verde (Agathón)
The recent pandemic crisis has highlighted the widespread condition of ‘polycrysis’ in which the impacts of climate change, air pollution, and health risks coincide. This leads to a vulnerability of urban systems that threaten lifestyles, economies, and the survival of individuals. To coexist with such scenarios that will characterize the near future, multiple environmental adaptation actions are necessary to counteract impacts and damage to the urban and building scale. The contribution proposes an analysis of the evolution of possible scenarios and strategies for environmental adaptation as a response to impacts. It prefigures project actions aimed at reducing the damage resulting from the current condition of overlapping risks, identifying in the crisis new opportunities for an ecological transition of urban districts as a long-term goal for sustainable development.